Excitonic splitting and vibronic coupling analysis of the m-cyanophenol dimer - Balmer, Franziska Andrea; Kopec, Sabine; Köppel, Horst (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2017)
The S1/S2 splitting of the m-cyanophenol dimer, (mCP)2 and the delocalization of its excitonically coupled S1/S2 states are investigated by mass-selective two-color resonant two-photon ionization and dispersed fluorescence spectroscopy, complemented by a theoretical vibronic coupling analysis based on correlated ab initio calculations at the approximate coupled cluster CC2 and SCS-CC2 levels. The calculations predict three close-lying ground-state minima of (mCP)2: The lowest is slightly Z-shaped (Ci-symmetric); the second-lowest is <5 cm-1 higher and planar (C2h). The vibrational ground state is probably delocalized over both minima. The S0 → S1 transition of (mCP)2 is electric-dipole allowed (Ag → Au), while the S0 → S2 transition is forbidden (Ag → Ag). Breaking the inversion symmetry by 12C/13C- or H/D-substitution renders the S0 → S2 transition partially allowed; the excitonic contribution to the S1/S2 splitting is Δexc = 7.3 cm-1. Additional isotope-dependent contributions arise from the changes of the m-cyanophenol zero-point vibrational energy upon electronic excitation, which are Δiso(12C/13C) = 3.3 cm-1 and Δiso(H/D) = 6.8 cm-1. Only partial localization of the exciton occurs in the 12C/13C and H/D substituted heterodimers. The SCS-CC2 calculated excitonic splitting is Δel = 179 cm-1; when multiplying this with the vibronic quenching factor Γvibronexp = 0.043, we obtain an exciton splitting Δvibronexp = 7.7 cm-1, which agrees very well with the experimental Δexc = 7.3 cm-1. The semiclassical exciton hopping times range from 3.2 ps in (mCP)2 to 5.7 ps in the heterodimer (mCP-h)·(mCP-d). A multimode vibronic coupling analysis is performed encompassing all the vibronic levels of the coupled S1/S2 states from the v = 0 level to 600 cm-1 above. Both linear and quadratic vibronic coupling schemes were investigated to simulate the S0 → S1/S2 vibronic spectra; those calculated with the latter scheme agree better with experiment.
Publication date (Web): December 6, 2016
Gesehen am 13.09.2018